INTRAOSSEOUS LIPOMA OF THE CALCANEUS: CASE REPORT OF A RARE BENIGN BONE TUMOR (Vietnam Journal of Community Medicine, 2026)
Intraosseous lipoma is one of the rarest primary bone tumors in the body. The reported incidence rate is